Świadczenia II filaru zabezpieczenia emerytalnego w Polsce w kontekście podstawowych idei ubezpieczeń społecznych - Łyskawa, Krzysztof (Benefits from the Polish pension eystem capital pillar in the context of general ideas of social insurance, 2006)
The loss of capacity to find employment in advanced age has been a problem for many centuries. Persons in advanced age were taken care of in a natural way by their families and church institutions. However, as late as in the period of industrial revolution, this phenomenon has taken on such dimensions that a need appeared to create pension insurance, both as state managed institutions and programs as well as private one (or of an association). The evolution of insurance institutions is also the evolution of ideas of social insurance. The main problem in Polish pension system is how paying benefits from the capital pillar. Group life insurance with capital fund and tontines could increase the realization of social risks.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 283-293